Mapping the Evolution of Genre-Based Approaches in Teaching Writing: A Bibliometric Perspective - Handayani, Azizah; Bau, Sri Liliska R.; Nabu, Andiani (English Education Department, 2023)
This study investigates the Genre-Based Approach to Teaching Writing, as reported in English language education journals in Indonesia from 2018 to 2022, based on SINTA rankings 1 to 4. The research predominantly employs qualitative and quantitative methods, with less frequent use of Classroom Action Research (CAR) and Research and Development (R&D) approaches. The review highlights a peak in research activity in 2020, likely due to adaptations required by the COVID-19 pandemic. The findings reveal that the genre-based approach has evolved from a niche method to a mainstream educational strategy, demonstrating its effectiveness in improving students' writing skills through structured genre-specific instruction. Data collection methods varied across studies, with questionnaires being the most commonly used instrument, supplemented by observation tests and interviews. The research indicates significant improvements in writing abilities, supported by diverse methodological approaches including empirical evidence and iterative improvements. The study provides a comprehensive overview of key research trends, influential publications, and emerging themes, offering valuable insights for educators, researchers, and policymakers. By mapping the development of genre-based approaches, this research contributes to a deeper understanding of its impact on writing education and informs future research directions.